PERAN APARATUR PERTANIAN DALAM PEMASARAN PRODUKSI JAGUNG PETANI MELALUI PENDEKATAN ANALISIS SWOT DI KABUPATEN JENEPONTO - Hendrawati Hamid (POLITEKNIK LP3I JAKARTA, 2025)
This study aim to analyze the marketing strategies of corn production by farmers in Jeneponto Regency. The research method used is a qualitative descriptive approach, using the strengths, weaknesses, opportunities, threats (SWOT) analysis related to corn marketing that has been carried out so far, primary data was obtained from the results of in-depth interviews with several informants, namely: Head of Service, Head of related Divisions, Agricultural Service officials, Agricultural Extension Workers, and administrators and members of farmer groups. In addition, observations were also carried out on site, and literature studies, as well as conducting FGD (focus discussion groups) with various related parties. The results of the study found through the SWOT analysis matrix on the four corn marketing strategies are, S-O strategy: Establishing good communication between farmers, the government and traders for marketing information, W-O strategy: The need for government support in developing infrastructure and transportation to overcome the distance of farming locations, S-T strategy: Making marketing channels effective with adequate transportation, W-T strategy: Education and access to market price information.